2015
DOI: 10.1016/j.urology.2014.07.075
|View full text |Cite
|
Sign up to set email alerts
|

Sports-related Genitourinary Injuries Presenting to United States Emergency Departments

Abstract: OBJECTIVE To describe epidemiologic features of sports-related genitourinary (GU) injuries and determine patient cohorts and particular sporting activities associated with increased GU injury risk. MATERIALS AND METHODS The National Electronic Injury Surveillance System, a data set validated to provide a probability sample of injury-related US emergency department (ED) presentations, was analyzed to characterize GU injuries between 2002 and 2010. A total of 13,851 observations were analyzed to derive nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…5 Cutting the median bar of the zip with bone or wire cutters to separate the two faceplates and release entrapped skin is one known method. 6 Others have noted that complete separation of the faceplates can be difficult and have therefore proposed limited separation of these elements to relieve entrapment.…”
Section: Discussionmentioning
confidence: 99%
“…5 Cutting the median bar of the zip with bone or wire cutters to separate the two faceplates and release entrapped skin is one known method. 6 Others have noted that complete separation of the faceplates can be difficult and have therefore proposed limited separation of these elements to relieve entrapment.…”
Section: Discussionmentioning
confidence: 99%
“…Most blunt scrotal trauma is sporting-related and occurs in males between the ages of 3 and 45 year old. 6 Congeni and colleagues surveyed 755 male high school and collegiate athletes on genitourinary injury awareness. Up to 47% of high school and collegiate athletes reported not wearing genitourinary protective gear during sporting activity and only one-third reported that they would seek medical attention for testicular pain and swelling.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the NEISS uses validated algorithms created by the CPSC, utilizing cluster variables and sample weighting to calculate estimates of national injury incidence totals for large‐scale data interpretation. Secondary to these strengths, the NEISS has been utilized in numerous analyses spanning a variety of medical specialties …”
Section: Methodsmentioning
confidence: 99%